Una Mistica Clarissa Nella Firenze Del Seicento: Maria Angiola Gini (1631-1664) fra carismi e simulata santità - Zangari, Mattia (Miscellanea francescana, 2024)
The aim of this work is to sketch both the figure and the spiritual experience of Sister Maria Angiola Gini (1631-1664), a mystic Poor Clare of the nunnery of St. Matteo (in Arcetri, Florence). The author turns to hagiography on the one hand, and to epistolary and processual sources on the other, in an attempt to shed light on Gini's evocative story. The overall impression is that we're dealing with a case of "pretended sanctity", which is worth detecting further, given the wealth of unpublished material.